Increased Lacrimal Fluid Level of HMGB1 in Vernal Keratoconjunctivitis. (4th July 2019) - Caputo, Roberto; Pasti, Mattia; de Libero, Cinzia; Mori, Francesca; Barni, Simona; Danti, Gioia; Buonvicino, Daniela; Urru, Matteo; Chiarugi, Alberto; Pucci, Neri
ABSTRACT: Purpose : The aim of the present prospective study was to evaluate the lacrimal fluid concentration of HMGB1 in young patients affected by Vernal Keratoconjunctivitis (VKC) compared to a control group of healthy subjects of same age. Methods : Tear fluids was collected in a group of VKC patients and compared to a control group of healthy subjects. HMGB1 concentration was measured using the HMGB1 ELISA II test both in VCK and control subjects. Results : The mean concentration of HMGB1 in tear fluids of 45 VKC patients was 0, 977 ± 0, 72 ng/ml whereas in the control group was 0, 24 ± 0, 25 ng/ml and the difference was statistically significant (p = 0, 000106) Conclusion : The concentration of HMGB1 in VCK patients was found to be significantly increased, suggesting a possible role of this protein in the inflammatory mechanism of VKC.